Cash transfers, employment and informality in South Africa - (:unkn) unknown (My University, 2019)
This dissertation studies the employment effects of cash transfers in a segmented labor market. The first and main chapter shows that an unconditional cash transfer program targeted at mothers has lasting positive impacts on job quality. Five years after having received the cash transfer, treated mothers are more likely to be employed in the formal sector. This appears to be the result of changes in the way recipients search for a job, as treated mothers are unemployed for longer and target better jobs. The second chapter shows the employment effects of a reform in the means-tested, non-contributory pension system of South Africa, which lowered the age of retirement from 65 to 60 for men. The reform caused a large extensive-margin response, as informal workers stop working when they become eligible to the pension. Instead, formal workers do not quit their jobs nor switch to the informal sector to become eligible to the pension. Lastly, this dissertation discusses the lack of self-employment in South Africa. Building on the results of the first two chapters, the last chapter shows that South Africans do not increase entry to self-employment as a result of cash transfers. This indicates that liquidity constraints are not the main reason for the lack of self-employment in South Africa, which is likely to have historical roots stemming from Apartheid. The chapter discusses evidence and potential policy implications of this explanation, alongside possible avenues for future research on this phenomenon.
Keywords: African Research